(untitled) (Medico Legal Update, 2021)
Background: Silent cerebral infarction is frequently encountered on various imaging modalities of brain in individuals with atrial fibrillation, its exact relation with atrial fibrillation is still debated. Objectives: The study was carried out to estimate the link between silent cerebral infarcts with atrial fibrillation, both paroxysmal and persistent types. Materials and Method. A random sample of 150 were included in the study, 100 with atrial fibrillation 50 case with paroxysmal, 50 case with persistent type, and 50 control, for both cases and control a questionnaire was constructed, physical examination, neurological examination, and magnetic resonance imaging were done. Results: Mean age was 64.6667. Of the total sample there was 96 males and 54 females. 89 individual of the total sample had silent cerebral lesion while 61 had no lesion. Of those who had lesions, 38 individuals had paroxysmal atrial fibrillation, 41 had persistent atrial fibrillation, and only 10 individuals belong to control group. There was high statistically significant difference between group of cases with atrial fibrillation and group of control in sinus rhythm where p value is 0.0001. Conclusion: Both paroxysmal and persistent atrial fibrillation is associated with heightened hazard of silent cerebral infarctions.